Weather-resistant anti-icing fluorosilicon composite coating and preparation method thereof

CN123004255APending Publication Date: 2026-10-30SICHUAN PENGSHAN XINGYUAN SPECIAL COATING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611154327.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明所要解决的技术问题在于提供一种耐候防结冰氟硅复合涂料及其制备方法,通过羟基封端高耐候氟素树脂与氟改性有机硅树脂的基体复配,结合金刚石微粉与气相二氧化硅构建耐磨微纳二元粗糙结构,解决现有防结冰涂料耐候性不佳、抗磨损能力差以及防结冰长效性不足的问题

Benefits of technology

(1)低表面能与微纳粗糙结构协同防冰:氟素树脂的高氟含量与氟改性有机硅树脂的-Si-O-Si-骨架协同提供低表面能(<20mN/m),金刚石微粉(微米级凸起)与气相二氧化硅(纳米级凸起)构建微米-纳米二级粗糙结构,使水滴处于Cassie-Baxter状态,涂层的冰附着强度低至18kPa~22kPa。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004255A_ABST
    Figure CN123004255A_ABST
Patent Text Reader

Abstract

The application discloses weather-resistant anti-icing fluorosilicon composite coating and a preparation method thereof. The coating comprises, by weight, 30-45 parts of hydroxyl-terminated high-weather-resistant fluorine resin, 15-25 parts of fluorine-modified silicone resin, 5-12 parts of diamond micro powder, 3-8 parts of hydrophobic fumed silica, 1.5-3.5 parts of silane coupling agent, 8-15 parts of hexamethylene diisocyanate trimer curing agent and 20-30 parts of solvent. The preparation method comprises the following steps: after the diamond micro powder and the fumed silica are pretreated by surface coupling with the silane coupling agent, the diamond micro powder and the fumed silica are mixed and ground with the fluorine resin and the fluorine-modified silicone resin, and then the curing agent is added for coating and curing. The diamond micro powder and the fumed silica are used to construct a wear-resistant micro-nano binary rough structure, and the fluorosilicon double resin is used to realize the synergistic effect of low surface energy, so that the coating has low ice adhesion strength, high wear resistance and excellent weather resistance, and is suitable for the anti-icing protection of outdoor facilities such as wind power blades and power transmission lines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of anti-icing coating technology, specifically relating to a weather-resistant and anti-icing fluorosilicone composite coating with hydroxyl-terminated high weather-resistant fluorine resin and fluorine-modified organosilicon resin as the base resin, and diamond micro powder and fumed silica to construct a wear-resistant micro-nano rough structure, as well as the preparation method thereof. It is suitable for the surfaces of facilities such as wind turbine blades, transmission lines, bridge cables, and communication towers that are exposed to low temperature and high humidity environments and have strict requirements for weather resistance. Background Technology

[0002] Outdoor facilities such as power transmission lines, wind turbine blades, photovoltaic modules, and communication towers are prone to surface icing in cold or high-humidity winter environments, which may lead to serious safety accidents such as tower collapse, line breakage, wind turbine shutdown, or mechanical overload.

[0003] Existing anti-icing coatings mostly rely on low surface energy silicone resins or fluorocarbon resins. However, silicone resins alone have poor mechanical strength and weather resistance, and are prone to aging and degradation under long-term outdoor ultraviolet radiation; while fluorocarbon resins alone have excellent weather resistance, their flexibility and adhesion are limited, and their micro-rough structure is easily damaged and fails under the abrasion of wind and sand or the shear stress of ice layer peeling, resulting in a rapid decline in anti-icing performance.

[0004] In the prior art, CN104530974B discloses an anti-icing coating scheme composed of fluorosilicone resin and nano-silica / alumina, but its surface micro-nano structure has insufficient long-term wear resistance, and its hydrophobic properties degrade rapidly under actual working conditions such as wind and sand erosion. CN115678359A discloses an anti-icing fluorocarbon coating composed of tetrafluoropolymer resin and organosilicon water-repellent additives, but it does not involve the technical concept of constructing a wear-resistant skeleton with high-hardness micron fillers.

[0005] Therefore, how to make anti-icing coatings have low ice adhesion strength, excellent mechanical abrasion resistance and long-term weather resistance is a technical problem that urgently needs to be solved. Summary of the Invention

[0006] The technical problem to be solved by this invention is to provide a weather-resistant and anti-icing fluorosilicone composite coating and its preparation method. By compounding a matrix of hydroxyl-terminated high weather-resistant fluorine resin and fluorine-modified organosilicon resin, and combining diamond micro powder and fumed silica to construct a wear-resistant micro-nano binary rough structure, this invention solves the problems of poor weather resistance, poor wear resistance and insufficient long-term anti-icing effect of existing anti-icing coatings.

[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: In a first aspect, a weather-resistant and anti-icing fluorosilicone composite coating is provided, comprising the following components by weight: 30-45 parts of hydroxyl-terminated, highly weather-resistant fluorinated resin 15-25 parts of fluorine-modified organosilicon resin, Five to twelve parts of diamond micropowder, after surface coupling pretreatment with a silane coupling agent, had an average particle size D50 of 1.5 μm to 3.0 μm and a Mohs hardness of 10. 3-8 parts of hydrophobic fumed silica after surface coupling pretreatment with silane coupling agent. 1.5–3.5 parts of silane coupling agent, 8-15 parts of curing agent, Solvent 20-30 parts.

[0008] Specifically, the specific surface area of ​​the hydrophobic fumed silica is 150 m². 2 / g~250m 2 / g, with a native particle size of 15nm~30nm.

[0009] Specifically, the hydroxyl-terminated high weather-resistant fluorine resin has a hydroxyl value of 40mgKOH / g to 60mgKOH / g and a fluorine content of ≥25wt%; the fluorine-modified organosilicon resin is a fluoroalkyl-modified polysiloxane with a solid content of 60%.

[0010] Specifically, the silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane or γ-aminopropyltriethoxysilane.

[0011] Specifically, the curing agent is hexamethylene diisocyanate trimer with an NCO content of 21wt% to 22wt%.

[0012] Specifically, it also includes 0.5 to 1.5 parts of acrylic block copolymer dispersant and 0.2 to 0.8 parts of fluorocarbon modified polyether leveling agent.

[0013] Secondly, a method for preparing a weather-resistant and anti-icing fluorosilicone composite coating is provided, characterized by comprising the following steps: S1. Pre-treatment of filler surface coupling: Diamond micro powder and hydrophobic fumed silica pre-treated with silane coupling agent are added to a reaction vessel containing some solvent and silane coupling agent. The mixture is heated to 70℃~75℃ and stirred for 2 hours. The ultrasonic dispersion time is 30 minutes to obtain modified filler slurry. S2. Grinding and mixing of main agent: Mix hydroxyl-terminated high weather-resistant fluorine resin and fluorine-modified organosilicon resin evenly, add the modified filler slurry, dispersant, leveling agent and remaining solvent, grind until the fineness is less than 15μm, filter and discharge to obtain the main agent component; S3. Preparation and coating curing: Mix the main component and curing agent evenly at a molar ratio of isocyanate to hydroxyl groups of 1.05:1, coat the mixture onto the substrate surface, and cure to form an anti-icing coating.

[0014] Specifically, in step S3, the curing conditions are baking and curing at 80°C for 1 hour or curing at room temperature for 7 days, and the dry film thickness is 35μm~50μm.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Low surface energy and micro-nano rough structure work together to prevent ice: The high fluorine content of fluorine resin and the -Si-O-Si- skeleton of fluorine modified organosilicon resin work together to provide low surface energy (<20mN / m). Diamond micro powder (micron-level protrusions) and fumed silica (nano-level protrusions) construct a micron-nano secondary rough structure, so that water droplets are in the Cassie-Baxter state, and the ice adhesion strength of the coating is as low as 18kPa~22kPa.

[0016] (2) High wear resistance: Due to the inherent high hardness of diamond micro powder with a Mohs hardness of 10, wear-resistant bump skeletons are formed on the coating surface to resist wind and sand erosion and mechanical friction. After 500 cycles of Taber wear, the ice adhesion strength is still below 25 kPa.

[0017] (3) High weather resistance: The high bond energy of fluorocarbon bonds (CF about 485kJ / mol) gives the main chain resin excellent resistance to ultraviolet degradation. After 2000 hours of QUVA ultraviolet accelerated aging, the gloss retention rate is greater than 92%.

[0018] (4) Good adhesion: The alkoxy groups of the silane coupling agent condense with the surface of the inorganic filler, and the organic functional groups are intertwined with the resin cross-linking network, realizing the chemical bonding of the inorganic-organic interface, and the coating adhesion reaches level 0 (cross-cut test). Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0020] Figure 1 This is a schematic diagram of the cross-sectional micro / nano structure of the anti-icing fluorosilicone composite coating in an embodiment of the present invention. Detailed Implementation

[0021] It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of the invention.

[0022] The following detailed description of the implementation method of the present invention is in conjunction with the accompanying drawings. The description is only a partial embodiment and not all embodiments. For clarity, representations and descriptions unrelated to the present invention are omitted in the drawings and description.

[0023] To provide a clearer understanding of the technical features, objectives, and beneficial effects of this invention, the following detailed description of the technical solution is provided. Obviously, the described embodiments are only a portion of the embodiments of this invention, not all of them, and should not be construed as limiting the scope of implementation of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention.

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below with reference to specific embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0025] Example 1: A weather-resistant and anti-icing fluorosilicone composite coating, composed of the following components by weight: 100 parts of hydroxyl-terminated high weather-resistant fluorine resin (hydroxyl value 60 mg KOH / g, fluorine content 25 wt%) 20 parts of fluorine-modified silicone resin (trifluoropropyl-modified polysiloxane, solid content 60%) Eight parts of diamond micron powder (D50=2.0μm). Hydrophobic fumed silica (specific surface area 200m²) 2 5 parts ( / g, original particle size 20nm), 2.5 parts of γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) 1.0 part of acrylic block copolymer dispersant, 0.5 parts of fluorocarbon modified polyether leveling agent, 11 parts of hexamethylene diisocyanate trimer curing agent (NCO content 21.8wt%) 25 parts of a mixed solvent of butyl acetate and xylene (mass ratio 1:1).

[0026] Preparation method: Diamond micro powder and hydrophobic fumed silica are added to a reactor containing half of the mixed solvent and silane coupling agent. The mixture is ultrasonically dispersed for 30 minutes, heated to 70℃, and stirred for 2 hours to obtain a modified filler slurry. Hydroxyl-terminated high-weather-resistant fluorine resin and fluorine-modified silicone resin are added to a mixing tank and mixed evenly. The modified filler slurry, dispersant, leveling agent, and remaining solvent are added, and the mixture is transferred to a sand mill and ground at 2500 rpm for 45 minutes until the fineness is less than 15 μm. The mixture is then filtered to obtain the main component. Before application, the main component and HDI trimer curing agent are mixed evenly at an NCO / OH molar ratio of 1.05:1. After degassing, the mixture is sprayed onto a sandblasted (Sa2.5 grade) carbon steel substrate. The dry film thickness is controlled at 40 μm, and the film is baked at 80℃ for 1 hour for curing.

[0027] Example 2 differs from Example 1 in that it contains 40 parts of hydroxyl-terminated high-weather-resistant fluorine resin (hydroxyl value 50 mg KOH / g, fluorine content 30 wt%), 15 parts of fluorine-modified silicone resin, 12 parts of diamond micron powder (D50 = 1.5 μm), 3 parts of hydrophobic fumed silica, 3.5 parts of silane coupling agent (KH-550), 1.2 parts of dispersant, 0.5 parts of leveling agent, 12 parts of curing agent, and 25 parts of mixed solvent. The preparation method is the same as in Example 1.

[0028] Example 3 differs from Example 1 in that: 30 parts of hydroxyl-terminated high-weather-resistant fluorine resin, 25 parts of fluorine-modified organosilicon resin (perfluorodecyl modified), 5 parts of diamond micron powder (D50=3.0μm), and 8 parts of hydrophobic fumed silica (specific surface area 150m²). 2 / g), 1.5 parts of silane coupling agent (KH-570), 0.8 parts of dispersant, 0.5 parts of leveling agent, 10 parts of curing agent, and 25 parts of mixed solvent. The preparation method is the same as in Example 1.

[0029] Comparative Example 1 (without diamond micron powder) differs from Example 1 in that diamond micron powder is not used, and the amount of hydrophobic fumed silica is increased to 13 parts to keep the total amount of filler unchanged.

[0030] Comparative Example 2 (monofluororesin, fluorine-free modified silicone resin) differs from Example 1 in that: fluorine-modified silicone resin is not used, and the amount of hydroxyl-terminated high weather-resistant fluorine resin is increased to 55 parts.

[0031] Comparative Example 3 (without silane coupling agent) differs from Example 1 in that it does not use silane coupling agent.

[0032] Performance testing was conducted on the coatings prepared in Examples 1-3 and Comparative Examples 1-3 as described above: Water contact angle: Measured using a contact angle meter with a droplet volume of 3 μL at room temperature.

[0033] Ice adhesion strength: The maximum force required to pull an ice column off the coating surface is determined by the pull-out method at -15℃, and the ice adhesion strength is obtained by dividing the force by the bottom area of ​​the ice column.

[0034] Ice adhesion strength after Taber wear: The ice adhesion strength was measured after 500 cycles using a CS-10 grinding wheel with a 1000g load.

[0035] Adhesion: Determined by cross-cut test according to GB / T 9286 standard.

[0036] QUVA aging gloss retention rate: After 2000 hours of QUVA accelerated aging, the gloss retention rate at 60° was measured.

[0037] The test results are shown in the table below: Table 1: Test Results Table

[0038] The test results show that the water contact angle of the coatings in Examples 1-3 of this invention is greater than 115°, the ice adhesion strength is less than 22 kPa, and the ice adhesion strength remains below 25 kPa after 500 Taber abrasion cycles. The adhesion is grade 0 for all examples, and the gloss retention rate is greater than 92% after 2000 hours of QUVA aging. Comparative Example 1, lacking diamond micropowder, showed a sharp increase in ice adhesion strength to 78 kPa after abrasion, demonstrating that diamond micropowder is crucial for maintaining the wear resistance of the micro-nano rough structure. Comparative Example 2, lacking fluorine-modified silicone resin, showed an increase in ice adhesion strength to 42 kPa and a decrease in adhesion to grade 2, demonstrating the synergistic effect of the fluorine-silicone dual resin composite in reducing surface energy and improving adhesion. Comparative Example 3, lacking silane coupling agent, showed a decrease in adhesion to grade 3 and a decrease in gloss retention rate to 82% after aging, demonstrating the key role of silane coupling agent in the inorganic-organic interface bonding and the overall durability of the coating.

[0039] The above description is merely a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the concept described herein through the above teachings or related technologies or knowledge. Modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. A weather-resistant and anti-icing fluorosilicone composite coating, characterized in that, The following components are included in parts by weight: 30-45 parts of hydroxyl-terminated, highly weather-resistant fluorinated resin 15-25 parts of fluorine-modified organosilicon resin, Five to twelve parts of diamond micropowder, after surface coupling pretreatment with a silane coupling agent, had an average particle size D50 of 1.5 μm to 3.0 μm and a Mohs hardness of 10. 3-8 parts of hydrophobic fumed silica after surface coupling pretreatment with silane coupling agent. 1.5–3.5 parts of silane coupling agent, 8-15 parts of curing agent, Solvent 20-30 parts.

2. The weather-resistant and anti-icing fluorosilicone composite coating according to claim 1, characterized in that, The specific surface area of ​​the hydrophobic fumed silica is 150 m². 2 / g~250m 2 / g, with a native particle size of 15nm~30nm.

3. The weather-resistant and anti-icing fluorosilicone composite coating according to claim 1, characterized in that, The hydroxyl-terminated high weather-resistant fluorine resin has a hydroxyl value of 40mgKOH / g to 60mgKOH / g and a fluorine content of ≥25wt%; the fluorine-modified organosilicon resin is a fluoroalkyl-modified polysiloxane with a solid content of 60%.

4. The weather-resistant and anti-icing fluorosilicone composite coating according to claim 1, characterized in that, The silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane or γ-aminopropyltriethoxysilane.

5. The weather-resistant and anti-icing fluorosilicone composite coating according to claim 1, characterized in that, The curing agent is hexamethylene diisocyanate trimer with an NCO content of 21wt% to 22wt%.

6. The weather-resistant and anti-icing fluorosilicone composite coating according to any one of claims 1, characterized in that, It also includes 0.5 to 1.5 parts of acrylic block copolymer dispersant and 0.2 to 0.8 parts of fluorocarbon modified polyether leveling agent.

7. A method for preparing the weather-resistant and anti-icing fluorosilicone composite coating according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Pretreatment of filler surface coupling: Diamond micro powder and hydrophobic fumed silica are added to a reaction vessel containing some solvent and silane coupling agent. The mixture is heated to 70℃~75℃ and stirred for 2 hours. The ultrasonic dispersion time is 30 minutes to obtain modified filler slurry. S2. Grinding and mixing of main agent: Mix hydroxyl-terminated high weather-resistant fluorine resin and fluorine-modified organosilicon resin evenly, add the modified filler slurry, dispersant, leveling agent and remaining solvent, grind until the fineness is less than 15μm, filter and discharge to obtain the main agent component; S3. Preparation and coating curing: Mix the main component and curing agent evenly at a molar ratio of isocyanate to hydroxyl groups of 1.05:1, coat the mixture onto the substrate surface, and cure to form an anti-icing coating.

8. The method for preparing the weather-resistant and anti-icing fluorosilicone composite coating according to claim 7, characterized in that, In step S3, the curing conditions are baking at 80°C for 1 hour or curing at room temperature for 7 days, and the dry film thickness is 35μm~50μm.

Citation Information

Patent Citations

  • A kind of anti-icing paint and its preparation method and application

    CN104530974B

  • Preparation method of anti-icing fluorocarbon coating for wind power blade

    CN115678359A